HUBUNGAN ANTARA TINGKAT KINERJA PENYULUH PERTANIAN LAPANGAN DAN KEPUASAN PETANI DI KECAMATAN LOA JANAN ILIR KOTA SAMARINDA (The Relationship between Performance Level of Field Agriculture Instructor and Farmer Satisfaction in Loa Janan Ilir Subcity Samarinda City) - MAKSUM MAKSUM; MUHAMMAD ERWAN SURIAATMAJA (Universitas Mulawarman (University of Mulawarman), 2020)
The performance level of Field Agriculture Instructor (FAI) is the level of FAI success in carrying out their duties. The level of satisfaction is the difference between expectation and performance performed. The purposes of this study were to determine FAI performance level, farmer satisfaction level, and the relationship between the FAI performance level and farmer satisfaction in Loa Janan Ilir Subcity, Samarinda City. This research was conducted from May to July 2019. The research location was in Loa Janan Ilir Subcity, Samarinda City. The sampling method used is the simple random sampling method with total respondents of 42 farmers. Data analysis was done by the correlation test of Rank Spearman and t test. The results of this research showed that the FAI performance level in Loa Janan Ilir Subcity, Samarinda City was quite good with a score of 67.5. Farmers were satisfy to FAI performance in Loa Janan Ilir Subcity with total score 67.35. There is a strong relationship and significant between the FAI performance level and farmer satisfaction in Loa Janan Ilir District based on rscount = 0.63 and tcalculated > ttable (5.15 ˃ 1.68).